Optimized DNA extraction and metagenomic sequencing of airborne microbial communities - Jiang, W.; Liang, P.; Wang, B.; Fang, J.; Lang, J.; Tian, G.; Jiang, J.; Jiang, J.
Metagenomic sequencing has been widely used for the study of microbial communities from various environments such as soil, ocean, sediment and fresh water. Nonetheless, metagenomic sequencing of microbial communities in the air remains technically challenging, partly owing to the limited mass of collectable atmospheric particulate matter and the low biological content it contains. Here we present an optimized protocol for extracting up to tens of nanograms of airborne microbial genomic DNA from collected particulate matter. With an improved sequencing library preparation protocol, this quantity is sufficient for downstream applications, such as metagenomic sequencing for sampling various genes from the airborne microbial community. The described protocol takes ~ 12 h of bench time over 2-3 d, and it can be performed with standard molecular biology equipment in the laboratory. A modified version of this protocol may also be used for genomic DNA extraction from other environmental samples of limited mass or low biological content.
Keywords: AIR POLLUTION; AIRBORNE MICROORGANISM; ARTICLE; CONTROLLED STUDY; DNA BINDING; DNA DETERMINATION; DNA EXTRACTION; DNA LIBRARY; DNA SEQUENCE; GENOME ANALYSIS; METAGENOMICS; MICROBIAL COMMUNITY; NONHUMAN; PARTICULATE MATTER; PRIORITY JOURNAL; PRIORITY JOURNAL; SEQUENCE ANALYSIS; BIOCHEMISTRY; CHINA; DEVICES; DNA SEQUENCE; ENVIRONMENTAL MONITORING; EQUIPMENT DESIGN; GENETICS; ISOLATION AND PURIFICATION; METAGENOME; MICROBIAL CONSORTIUM; MICROBIOLOGY; PROCEDURES; QUALITY CONTROL; WORKFLOW